2010
DOI: 10.1186/1746-1596-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical approach to the pathogenesis of clinical cases of Bovine Herpesvirus type 5 infections

Abstract: Meningoencephalitis by Herpesvirus type 5 (BoHV-5) in cattle has some features that are similar to those of herpetic encephalitis in humans and other animal species. Human Herpesvirus 3 (commonly known as Varicella-zoster virus 1), herpes simplex viruses (HSV), and equid Herpesvirus 1 (EHV-1) induce an intense inflammatory, vascular and cellular response. In spite of the many reports describing the histological lesions associated with natural and experimental infections, the immunopathological mechanisms for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Previous studies revealed that mitochondrial membrane potential can be altered without affecting non-transformed cellular cycle after infected by BHV5 (Brenner et al 2012;Garcia et al 2013). The expression of anti-oxidant protein-like 1 (AOP-1), a protective pathway, has been detected in bovine embryos and brain histological sections, both infected by BHV5 (Brenner et al 2012;Cardoso et al 2010). Furthermore, increase of mitochondrial membrane potential could be associated to virus replication and not always associated to cell death (Hay and Kannourakis 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies revealed that mitochondrial membrane potential can be altered without affecting non-transformed cellular cycle after infected by BHV5 (Brenner et al 2012;Garcia et al 2013). The expression of anti-oxidant protein-like 1 (AOP-1), a protective pathway, has been detected in bovine embryos and brain histological sections, both infected by BHV5 (Brenner et al 2012;Cardoso et al 2010). Furthermore, increase of mitochondrial membrane potential could be associated to virus replication and not always associated to cell death (Hay and Kannourakis 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, rabbits have been used as an animal model to study selected aspects of acute and latent infections caused by BoHV-5 [19]. Unlike BoHV-1, BoHV-5 can be difficult to isolate from cell culture and animals presenting neurological symptoms after experimental inoculation [20-23]. These difficulties in viral isolation might be related to low virus titres present in tissue sections [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been postulated that bovine herpesvirus 5 (BHV-5) entry the CNS is facilitated by leukocytes and MMP9. However, induction of MMP9 expression by BHV-5 has not been directly demonstrated so far [75].…”
Section: The Heterogeneous Molecule: Proteoglycanmentioning
confidence: 99%
“…The closely related EHV-4 did not efficiently infect these local immune cells, which might be the reason why EHV-4-induced viremia is rare [98]. It has been postulated that BHV-5 might use a similar invasive mechanism as EHV-1 and that BHV-5 entry into the CNS is facilitated by leukocytes and MMP9 [75]. Lymphocytemediated viral entry into the brain has also been demonstrated for HTLV-1 [70].…”
Section: The Heterogeneous Molecule: Proteoglycanmentioning
confidence: 99%